2019
DOI: 10.20473/juxta.v10i12019.38-43
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Breast Cancer 3-years Survival Rate Based on the Pathological Stages

Abstract: Introduction: The aims of this study was to determine the differences of  breast cancer survival rate based on Pathological stages.Methods: This study was conducted with a retrospective case control design using secondary data from Dr. Soetomo General Hospital's medical records. The technique used to take the samples was purposive sampling. The sample was 45 breast cancer patients in Dr. Soetomo General Hospital In January 2015, that able to be contacted again and had a medical record in the oncology center in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The limited study is known to observe survival for each stage IIIA, IIIB, and IIIC. Mursyidah et al [30] observed that the 5-year overall survival for stage IIIA, IIIB, and IIIC, respectively, were 71.4%, 53.8%, and 50%. The problem of inadequate local healthcare providers, therapeutic facilities, and accessibility to healthcare centers in Indonesia may explain the high number of advanced-stage (IIIB-IIIC) patients which may lower the overall survival in this study [6,10,24].…”
Section: Discussionmentioning
confidence: 99%
“…The limited study is known to observe survival for each stage IIIA, IIIB, and IIIC. Mursyidah et al [30] observed that the 5-year overall survival for stage IIIA, IIIB, and IIIC, respectively, were 71.4%, 53.8%, and 50%. The problem of inadequate local healthcare providers, therapeutic facilities, and accessibility to healthcare centers in Indonesia may explain the high number of advanced-stage (IIIB-IIIC) patients which may lower the overall survival in this study [6,10,24].…”
Section: Discussionmentioning
confidence: 99%
“…21 The lower-stage breast cancer patients had the best 3-year survival rates compared to the end-stage breast cancer patients. 22 This study examined 30 breast cancer patients who underwent CAF chemotherapy for three cycles to obtain a total of 90 cycles. Of the 30 patients, 24 people (80%) had neutropenia and 6 (20%) without neutropenia.…”
Section: Methodsmentioning
confidence: 99%
“…Despite substantial advances in breast cancer research over the last 20 years, a large proportion of patients will acquire metastatic illness. Unfortunately, metastatic breast cancer has not yet been cured [ 5 ]. TNM stage, histopathological type, histological grade, hormone receptors, and the number of mitotic pictures are prognostic variables that affect the survival of breast cancer patients, according to the consensus of the College of American Pathologists in 1999.…”
Section: Introductionmentioning
confidence: 99%
“…It ranges from stage I to stage IV. Stage III cancer has a 5-year life expectancy of 86 %, and it changes with each stage [ [5] , [6] , [7] ].…”
Section: Introductionmentioning
confidence: 99%